The Principle of Subsidiarity in European Rules for a Digital Single Market - Pazos Castro, Ricardo (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
This paper presents the principle of subsidiarity in European Union law, outlining its main characteristics and implications, and then examines to which extent the legislator has taken it into account when proposing or adopting rules aimed at achieving a digital single market, or on consumer protection. The goal is to determine whether three risks have materialized. First, a low degree of attention paid to subsidiarity. Second, a standardization of the remarks made about such principle, regardless of the type of regulatory act, the level of harmonization sought, or the subject matter regulated. And third, similar exhaustiveness in the older and the more recent texts, despite the greater length and detail of the latter.